God? : a debate between a Christian and an atheist - Craig, William Lane (Point/counterpoint series (Oxford, England), 2004)
"In God?, William Lane Craig and Walter Sinnott-Armstrong bring to the printed page two debates they held before live audiences, preserving all the wit, clarity, and immediacy of their public exchanges. With none of the opaque discourse of academic logicians and divinity-school theologians, the authors make claims and comebacks that cut with precision. Their arguments are sharp and humorous, as each philosopher strikes quickly to the heart of his opponent's case. For example, Craig claims that we must believe in God to explain objective moral values, such as why rape is wrong. Sinnott-Armstrong responds that what makes rape wrong is the harm to victims of rape, so rape is immoral even if there is no God."--Jacket